Frequency Considerations in GIC Applications - L. Trichtchenko (Space Weather)
Abstract Geomagnetically induced currents (GIC) are a phenomenon well known for its negative effects on the operations of power systems. To efficiently mitigate them requires different types of power system modeling, from GIC to alternating current harmonic generation, to three‐dimensional finite element models of transformers. GIC are initiated by variations of the geomagnetic field in the presence of the conductive Earth, that is, the geophysical variables characterized by continuous frequency spectra, making GIC also exhibit continuous spectra. In order to adequately estimate their variations and peak values for mitigation purposes, an analysis is required of how sampling rate and spectral frequency content impact the measured characteristics of GIC and harmonics. The study is based on the geomagnetic measurements and the power network data (i.e., GIC and harmonics) with high sampling rates recorded during two geomagnetic storms, March 31, 2001 and July 26–27, 2004. Availability of data covering both the source and the result of geomagnetic storm impacts on power grid allows (a) analysis of the influence of spectral content on adequate representation of both geomagnetic and geoelectric variations during the intervals with significant increases in GIC and harmonics and (b) identifying the sampling rate sufficient to usefully represent the network response presented as GIC and harmonics variations. In summary, the adequate sampling rate is suggested and the deficiencies associated with undersampling of the geoelectric and GIC variations are identified and discussed.